2D van der Waals materials for ultrafast pulsed fiber lasers: review and prospect. (3rd December 2021) - Zhang, Ya-ni; Song, Zhuo-ying; Qiao, Dun; Li, Xiao-hui; Guang, Zhe; Li, Shao-peng; Zhou, Li-bin; Chen, Xiao-han
Abstract: 2D van der Waals materials are crystals composed of atomic layers, which have atomic thickness scale layers and rich distinct properties, including ultrafast optical response, surface effects, light-mater interaction, small size effects, quantum effects and macro quantum tunnel effects. With the exploration of saturable absorption characteristic of 2D van der Waals materials, a series of potential applications of 2D van der Waals materials as high threshold, broadband and fast response saturable absorbers (SAs) in ultrafast photonics have been proposed and confirmed. Herein, the photoelectric characteristics, nonlinear characteristic measurement technique of 2D van der Waals materials and the preparation technology of SAs are systematically described. Furthermore, the ultrafast pulsed fiber lasers based on classical 2D van der Waals materials including graphene, transition metal chalcogenides, topological insulators and black phosphorus have been fully summarized and analyzed. On this basis, opportunities and directions in this field, as well as the research results of ultrafast pulsed fiber lasers based on the latest 2D van der Waals materials (such as PbO, FePSe3, graphdiyne, bismuthene, Ag2 S and MXene etc), are reviewed and summarized.